Evaluation of pediatric patients installed due to acute gastroenteritis - Orhan, Özhan; Bulut, Mehmet (The European Research Journal, 2023)
Objectives: Acute gastroenteritis is one of the most prevalent causes of death and morbidity in children and a significant health issue in Turkey, as well as developed and developing nations. The purpose of this study is to analyze retrospectively the patients with acute gastroenteritis who sought treatment at the Kızıltepe State Hospital in Mardin. Methods: This study was designed as a single-center retrospective study in which demographic variables were evaluated by taking fresh stool samples from the patients who applied to the Mardin Province Kızıltepe State Hospital between 01/11/2020 and 31/10/2021 with the complaint of diarrhea. The information of rotavirus, enteric adenovirus and amoeba viruses in stool samples was investigated by qualitative immunochromatographic test. The researcher assessed the research data utilizing the hospital's file archive materials and three factors set by the researcher. The researcher extracted the information about these factors from the patient files and stored it in a Microsoft Office Excel file. Results: According to the gender variable of the research participants, Amoeba positive rates were considerably higher in males than in girls (35.8% versus 22.6%, p = 0.046, respectively). According to the age groups variable, rotavirus antigen positive was statistically significantly greater in the 5-24 month age group compared to other age groups (p = 0.034). Similarly, Amoeba positive was statistically substantially higher in the 5-24 month age group compared to other age groups (p = 0.001). There was no significant variation between age groups in the distribution of adenovirus. According to the seasonal variable, rotavirus antigen positivity was most prevalent in the spring, and the difference between the spring and other seasons was statistically significant (p = 0.001), whereas amoeba positivity was most prevalent in the summer, with no statistically significant difference between the seasons (p = 0.003). The frequency of undiscovered variables was greater during the spring-summer months, and a statistically significant difference (p = 0.041) was identified between the groups. The seasonal variation in the prevalence of Adenovirus antigen positive was not statistically significant (p = 0.394). Conclusions: As a result, in poor and underdeveloped nations, it is among the top five causes of death in children under the age of five, in relation to acute gastroenteritis. Furthermore, the majority of these deaths may be minimized by preventative and prevention strategies. It is the responsibility of governments, health professionals, and families to foster a safe and healthy environment for all infants and children during their infancy and development. Community-based health strategies should be undertaken to lower the morbidity and death rates of millions of people worldwide who are exposed to harmful environmental conditions and malnutrition.